HUBUNGAN ANTARA KETERLIBATAN KERJA, PENGEMBANGAN KARIR, DAN LOYALITAS KERJA YANG DIMEDIASI OLEH MOTIVASI KERJA PEGAWAI - Rahmi, Maulidatun Nur; Suryatni, Mukmin (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.04.TAHUN.2025DO - 10.24843/EEB.2025.v14.i04.p01, 2025)
Human Resource Management (HRM) plays an important role in the success of organizations, including the public sector, such as the Marine and Fisheries Service. This study aims to analyze the effect of work involvement and career development on job loyalty with work motivation as a mediator. Using a quantitative approach and saturated sample technique, all 40 employees were sampled. The findings of this study reveal that work engagement and career development significantly and positively influence job loyalty, enhance work motivation, and reinforce loyalty. Work motivation proved to be an important mediator in the relationship. This study confirms the importance of work engagement, career development, and work motivation in increasing employee loyalty. Unlike previous studies that focus on the private sector or the direct effects of HRM, this research presents a new perspective through the interaction of variables with work motivation. The practical implication is the need for policies that support career development and work motivation. Research limitations include limited location coverage and few variables analyzed. Further research is recommended to expand the coverage area and add contextual variables and external factors.